Tandem hot-pin hot-plate draw system (1946)
Close-up view of a tandem hot-pin hot-plate draw system used at DuPont during the early stages of synthetic fiber production and research. The photograph has been marked with several hand-drawn lines to depict the passage of filament through the system. During production, draw rolls like those visible at the top of the machine were used to ensure that filaments were stretched uniformly before being wound onto bobbins. As part of the cold-drawing process, hot plates like the ones visible below the draw rolls were used to strengthen the fiber.
Keywords: Nylon; Textile fibers, Synthetic; Nylon--Testing; E.I. du Pont de Nemours & Company; Machinery